2020
DOI: 10.1021/jacs.0c04886
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Dye Sensitization of Nanocrystalline Mesoporous Thin Films

Abstract: Recent advances in our mechanistic understanding of dye-sensitized electron transfer reactions occurring at metal oxide interfaces are described. These advances were enabled by the advent of mesoporous thin films, comprised of anatase TiO 2 nanocrystallites, that are amenable to spectroscopic and electrochemical characterization in unprecedented molecular-level detail. The metal-to-ligand charge transfer (MLCT) excited states of Ru polypyridyl compounds serve as the dye sensitizers. Excited-state injection oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 180 publications
0
24
0
Order By: Relevance
“…Meyer et al suggested that, in addition to the iodide that injectsa ne lectron to Ru PS, another iodide anion should be close to stabilizet he iodine radical generated in the electron injection; they also demonstrated that hydrogen-bonding interactions with iodide by amide and amino functional groups is effective in improving electron injection. [44][45][46] In our Zr-RuCP 6 -Zr-RuP 6 @1 wt %Pt-TiO 2 nanoparticles, the surfaceZ r 4 + -phosphate groups could attract iodide anionsnear the surface, probablyb yelectrostatic interactions, leading to enhanced H 2 evolutionp hotocatalytic activity.…”
Section: Effectsofi Odide Concentration and Phosphate Ph Buffermentioning
confidence: 97%
“…Meyer et al suggested that, in addition to the iodide that injectsa ne lectron to Ru PS, another iodide anion should be close to stabilizet he iodine radical generated in the electron injection; they also demonstrated that hydrogen-bonding interactions with iodide by amide and amino functional groups is effective in improving electron injection. [44][45][46] In our Zr-RuCP 6 -Zr-RuP 6 @1 wt %Pt-TiO 2 nanoparticles, the surfaceZ r 4 + -phosphate groups could attract iodide anionsnear the surface, probablyb yelectrostatic interactions, leading to enhanced H 2 evolutionp hotocatalytic activity.…”
Section: Effectsofi Odide Concentration and Phosphate Ph Buffermentioning
confidence: 97%
“…In contrast, Sn25 and Sn50 exhibited the fastest 3 MLCT injection dynamics, owing to the greater driving force for injection and higher Ti DOS available as an acceptor. This is reasonable because a larger density of acceptor states is expected to increase the rate of electron transfer in the Marcus-Gerischer picture . While Sn75 also has a higher Ti DOS according to periodic DFT calculations, the slower relative 3 MLCT injection rates were more comparable to SnO 2 , which is in contrast to the high 1 MLCT injection amplitude observed in Sn75.…”
Section: Results and Discussionmentioning
confidence: 86%
“…This is reasonable because a larger density of acceptor states is expected to increase the rate of electron transfer in the Marcus-Gerischer picture. 36 While Sn75 also has a higher Ti DOS according to periodic DFT calculations, the slower relative 3 MLCT injection rates were more comparable to SnO 2 , which is in contrast to the high 1 MLCT injection amplitude observed in Sn75. Although the reason for this dichotomy is not entirely clear, it is plausible that injection from the 1 MLCT state is largely mediated by discrete surface states, while injection from the 3 MLCT is mediated by the band structure of the metal oxide.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 2 more Smart Citations